2015
DOI: 10.1007/s00394-015-1096-6
|View full text |Cite|
|
Sign up to set email alerts
|

Increased dietary levels of α-linoleic acid inhibit mammary tumor growth and metastasis

Abstract: These data support the anticancer effect of an ALA-enriched diet, which might be used as a dietary strategy in breast cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
0
44
0
1
Order By: Relevance
“…ALA is an essential omega3-PUFA, which is used to synthesize eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3). ALA is associated with antitumorigenic effects in mice fed with an ALA-rich diet [46] and was reported to be toxic for MCF7 cells causing cell cycle arrest and apoptosis through mitochondrial membrane depolarization [47]. In MCF7 cells, it was shown that exogenously added ALA decreased growth via estrogen receptor-mediated signaling [48].…”
Section: Resultsmentioning
confidence: 99%
“…ALA is an essential omega3-PUFA, which is used to synthesize eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3). ALA is associated with antitumorigenic effects in mice fed with an ALA-rich diet [46] and was reported to be toxic for MCF7 cells causing cell cycle arrest and apoptosis through mitochondrial membrane depolarization [47]. In MCF7 cells, it was shown that exogenously added ALA decreased growth via estrogen receptor-mediated signaling [48].…”
Section: Resultsmentioning
confidence: 99%
“…It is the precursor to long chain ω-3 fatty acids and is found in vegetable and seed oils such as flax and walnuts, as well as in beans, legumes, grains, and leafy vegetables. In animal studies, it was shown that increased dietary levels of alpha-linoleic acid inhibit mammary tumor growth and metastasis (210).…”
Section: Phytonutrients Modulation Of Cox-2 Expressionmentioning
confidence: 99%
“…Ten days post inoculation, when tumor was palpable 52 and reached approximately a volume of 100 mm 3 , mice (n = 50) were randomly divided into 5 groups and different formulations were injected by the lateral tail vein, during a short period of isoflurane-induced inhalation anesthesia. All animals were followed for 10 weeks or until the end point was reached.…”
Section: Gm1-ptx Treatmentmentioning
confidence: 99%
“…BALB/c mice were injected intramuscularly in the right thigh with 0.1 mL of LMM3 cell suspension (1 × 10 6 cells in MEM without serum and antibiotics) to generate the primary tumor. After tumor induction, mice were housed until palpable tumor was detected (7 days) 52 . Animals with tumor developed were included for subsequent experiments.…”
mentioning
confidence: 99%